2016
DOI: 10.1590/0100-67622016000200008
|View full text |Cite
|
Sign up to set email alerts
|

JUVENILE-MATURE GENETIC CORRELATIONS IN Pinus taeda CLONES PROPAGATED VIA SOMATIC EMBRYOGENESIS

Abstract: -This study aimed to estimate the genetic correlation among selection ages (juvenile -adult) and efficiency of early selection for the height, diameter, and volume traits of individuals from Pinus taeda families propagated via somatic embryogenesis. This study was carried out by genetic-statistical analysis, estimation procedure of variance (Reml), and prediction components of breeding values (Blup), using the Selegen-Reml/ Blup software. Genetic correlations among juvenile ages and rotation age were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…As correlações genéticas indicam que se a seleção for feita com base no DAP aos quatro anos de idade, haverá efeitos positivos de seleção tanto nesta variável quanto na altura das árvores aos oito anos de idade, dados os valores de iguais a 0,99 e 0,96, respectivamente (Tabela 7). Altas e positivas correlações fenotípicas e genéticas foram encontradas em P. caribaea var hondurensis aos 14 anos de idade (TAMBARUSSI et al, 2010), em Pinus radiata D. Don aos 12, 24 e 36 meses (DIAS et al, 2016) e em Pinus pinaster Aiton aos 17 anos (GASPAR et al, 2008).…”
Section: Correlações Entre Caracteres Viabilidade De Seleção Precoceunclassified
See 1 more Smart Citation
“…As correlações genéticas indicam que se a seleção for feita com base no DAP aos quatro anos de idade, haverá efeitos positivos de seleção tanto nesta variável quanto na altura das árvores aos oito anos de idade, dados os valores de iguais a 0,99 e 0,96, respectivamente (Tabela 7). Altas e positivas correlações fenotípicas e genéticas foram encontradas em P. caribaea var hondurensis aos 14 anos de idade (TAMBARUSSI et al, 2010), em Pinus radiata D. Don aos 12, 24 e 36 meses (DIAS et al, 2016) e em Pinus pinaster Aiton aos 17 anos (GASPAR et al, 2008).…”
Section: Correlações Entre Caracteres Viabilidade De Seleção Precoceunclassified
“…A eficiência da seleção em idade precoce em Pinus spp. também foi confirmada em outras espécies do gênero para caracteres silviculturais (PALUDZYSZYN FILHO et al, 2002;DIAS et al, 2016;COUTINHO et al, 2017). Entretanto há que se considerar que a eficiência da seleção precoce é garantida quando a seleção do material é feita em locais com condições edafoclimáticas semelhantes às dos locais onde os genótipos serão cultivados (COUTINHO et al, 2017).…”
Section: Correlações Entre Caracteres Viabilidade De Seleção Precoceunclassified
“…Correlations observed at early and late ages have suggested that different physiological mechanisms play key role at different development stages, a fact that can be attributed to different genes and expression mechanisms. However, the expression of these genes stabilizes over the years, as evidenced by high correlation between halfand full-rotation ages (Dias et al, 2016). There was decreasing correlation between ages, regardless of the age indicated for harvest (6, 10 or 20 years); the lowest values were recorded for selections held at juvenile ages.…”
Section: Discussionmentioning
confidence: 94%
“…There was decreasing correlation between ages, regardless of the age indicated for harvest (6, 10 or 20 years); the lowest values were recorded for selections held at juvenile ages. Dias et al (2016) worked with three different ages (1, 3 and 4 years) of clonal tests of P. Taeda propagated via somatic embryogenesis in Paraná and Santa Catarina states. Their results have shown that the lowest correlations observed among growth variables (DBH, H and VOL) were recorded between the youngest and the oldest evaluation ages.…”
Section: Discussionmentioning
confidence: 99%
“…Pinus pinaster, οιLepoittevin et al(2011) ανέφεραν ότι η φαινοτυπική και η γενετική συσχέτιση του ύψους με την περιφέρεια του κορμού ήταν στατιστικά σημαντικές (p<0,001) και ίσες με 0,86 και 0,82 αντίστοιχα.ΟιDias et al (2016), σε κλωνικό πείραμα Pinus taeda τεσσάρων ετών όμως, βρήκαν συντελεστές συσχέτισης μεταξύ ύψους και στηθιαίας διαμέτρου 0,523, ύψους και όγκου 0,456 και στηθιαίας διαμέτρου και όγκου 0,932, επιβεβαιώνοντας τη μεγαλύτερη συσχέτιση του όγκου με τη διάμετρο παρά με το ύψος.ΟιRoberds et al (2003) ενίσχυσαν τα γενικότερα αποτελέσματα, αφού σε απογονικό πείραμα 72 οικογενειών Pinus taeda τεχνητής επικονίασης 10-11 ετών εκτίμησαν τις γενετικές και φαινοτυπικές συσχετίσεις μεταξύ των αυξητικών γνωρισμάτων και τις βρήκαν θετικές και υψηλές. Οι φαινοτυπικές συσχετίσεις μεταξύ ύψους και διαμέτρου στο στηθιαίο ύψος και μεταξύ ύψους και όγκου ήταν ίσες με 0,62 και 0,73 αντίστοιχα.…”
unclassified